Culture initiation of Avicennia marina from Indonesia using two different culture media - Savitri, Wina Dian; Sunaryo, Patrick Anderson; Mitchel, Dennis; Hardjo, Popy Hartatie; Gultom, Mangihot Tua; Irawati, Fenny (Journal of Scientific Agriculture, 2024)
The grey mangrove population faces overexploitation, pollution, and global warming. Traditional propagation is challenging due to the recalcitrant seeds. The issues with Avicennia marina tissue culture are the browning of the explants and endophytes, which can affect the explants at any growing phase. This study aimed to produce and maintain A. marina explants until they developed into healthy plantlets. MS medium and WPM were used along with 0.4% PPM. Improving the survival, 400, 450, and 450 ppm PVP was also applied. The treatment using MS medium and WPM were compared, and the media enriched with 0.5 ppm BA and 1 ppm kinetin and no cytokinins were compared. The result showed that WPM+400 ppm PVP was better than MS medium (in any kind of treatment) in inducing shoots in A. marina (27%), as well as longer survival in in vitro conditions. In the MS media, all explants died after week 11, whereas in the WPM medium, three explants survived until week 16. In addition, most of the explants cultured in WPM exhibited no contamination until week 8, whereas in all treatments using MS media, there was contamination in the same week observed.